Epidemiological and geospatial characterization of goat leptospirosis in Northeast region of Brazil - Viana, Maira Pôrto; Dêvede da Silva, José; César Lima, Ana Milena; Fernandes Alves, Francisco Selmo; Pinheiro, Raimundo Rizaldo; Figueiredo da Costa, Diego; Pinheiro da Silva, Glaucenyra Cecília; Calado, Lucas Gonzales Lima Pereira; de Azevedo, Sérgio Santos; Alves, Clebert José (Elsevier, 2022)
The objective of this survey was to determine the seroprevalence of Leptospira spp., the most frequent serogroups, and the geospatial distribution in goats in seven states in the Northeast region of Brazil. Samples (n = 4,718) were collected in the states of Alagoas, Ceará, Maranhão, Paraíba, Piauí, Rio Grande do Norte and Sergipe and were analyzed using the microscopic agglutination test (MAT) with a cut-off point of 1:100. Additionally, geographic data were analyzed to construct epidemiological maps for characterization of leptospirosis in the municipalities with greater importance for goat farming in each state. Of the sampled animals, 17.7% were serologically reactive for Leptospira spp. Animal-level prevalence ranged within the states, from 7.07% (Alagoas) to 30.23% (Paraíba) with statistical difference (P < 0.001). For herds, 83.4% had at least one serologically reactive animal. Paraíba had the highest herd-level prevalence (98.36%) and Piauí the lowest (65.91%) (P < 0.001). The states of Ceará, Rio Grande do Norte, and Sergipe had 91.18%, 69.64%, and 92.59% of positive herds, respectively. The most frequently identified serogroups were Autumnalis (23.06%) and Australis (20.98%) and titers ranged from 100 to 1,600. In conclusion, leptospirosis is present in states in the Northeast region of Brazil, especially in environments with dry and deforested areas, demonstrating a possible adaptation of the infectious agent to areas of adverse climates and an apparent interspecies transmission. Also, it was possible to verify the circulation of serogroups that may be adapted to small ruminants maintained in semiarid conditions, causing the asymptomatic disease with reproductive losses.
Keywords: Epidemiology; Leptospira spp; Public Health; Semi-Arid; Zoonoses